2021
DOI: 10.3389/fcvm.2021.601470
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning to Prevent Acute Kidney Injury After Cardiac Surgery: A Meta-Analysis of Randomized Controlled Trials

Abstract: Objective: Randomized controlled trials (RCTs) evaluating the influence of remote ischemic preconditioning (RIPC) on acute kidney injury (AKI) after cardiac surgery showed inconsistent results. We performed a meta-analysis to evaluate the efficacy of RIPC on AKI after cardiac surgery.Methods: Relevant studies were obtained by search of PubMed, Embase, and Cochrane's Library databases. A random-effect model was used to pool the results. Meta-regression and subgroup analyses were used to determine the source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
(94 reference statements)
1
10
0
Order By: Relevance
“…Zarbock et al (122) conducted a large, multicenter, randomized, double-blind clinical trial in 2015, which suggested that remote ischemic preadaptation significantly reduced the incidence of major adverse renal events at 90 days in patients undergoing high-risk cardiac surgery compared to controls, while suggesting that remote ischemic preadaptation may promote renal recovery in patients with perioperative AKI. Similarly, the results of two recent metaanalyses confirm this view (123,124). However, like others, this conclusion still faces contrary opinions.…”
Section: Remote Ischemic Preadaptationmentioning
confidence: 69%
“…Zarbock et al (122) conducted a large, multicenter, randomized, double-blind clinical trial in 2015, which suggested that remote ischemic preadaptation significantly reduced the incidence of major adverse renal events at 90 days in patients undergoing high-risk cardiac surgery compared to controls, while suggesting that remote ischemic preadaptation may promote renal recovery in patients with perioperative AKI. Similarly, the results of two recent metaanalyses confirm this view (123,124). However, like others, this conclusion still faces contrary opinions.…”
Section: Remote Ischemic Preadaptationmentioning
confidence: 69%
“…It was shown that IPC ameliorated AKI induced by limb ischemia/reperfusion via inhibiting TLR4 and NF-κB signaling in rats [8]. A metaanalysis by Liu et al also supported the theory that remote ischemic preconditioning would effectively prevent AKI in patients after cardiac surgery [20]. However, the culminating events in the kidney after IPC are still ambiguous, especially in a crush syndrome model, which varies from typical ischemia-reperfusion injury models.…”
Section: Discussionmentioning
confidence: 99%
“…The different patterns observed in the muscle and in remote organs are possibly related to the underlying mechanisms of RIC. Longer cycles are necessary to activate different pathways supposed to be related to this technique and to evoke a protective effect in distant tissues, for instance, a neural pathway, in which sublethal ischemic stimulus provides an afferent signal to the central nervous system 16 , 20 , 21 . Consequently, there is an efferent response, through activation of parasympathetic nerves, that plays a role in modulating vascular activity and increasing anti-inflammatory substances 16 .…”
Section: Discussionmentioning
confidence: 99%